How to Engage with Younger Users on Instagram: A Comparative Analysis of HBO and Netflix in the Spanish and US Markets - Martín-Quevedo, Juan; Fernández-Gómez, Erika; Segado-Boj, Francisco (The International Journal on Media Management, 2021)
Social media have become useful tools for audiovisual promotion, especially to reach niche audiences. Twitter promotional strategies have been widely studied, yet other growing platforms such as Instagram have been less analyzed. This paper examines the Instagram promotional strategies of two pay-per-view platforms (HBO and Netflix) in two markets (the United States and Spain). A total of 731 messages, posted between May and November 2017, were analyzed to identify their formal features, objectives, and their content’s emotional and cognitive elements posted on HBO and Netflix’s Spanish and U.S. accounts. The results showed acute differences between how HBO and Netflix use their Instagram accounts in the two markets (Spain and the United States). The Spanish accounts mostly provided information, while the American accounts both provided information and promoted program content. Posts from U.S. accounts more frequently included links to social media, particularly to celebrity accounts. Spanish accounts relied more on diegetic images, whereas U.S. accounts emphasized non-diegetic and off-set images. Netflix used humor more than HBO did, and a stronger focus on celebrities. Humor and positive tone were found to be linked to higher engagement.
Keywords: audiences; television; networks; internet; entertainment media